2022
DOI: 10.1093/abm/kaac017
|View full text |Cite
|
Sign up to set email alerts
|

Daily Relations Between Stress and Electroencephalography-Assessed Sleep: A 15-Day Intensive Longitudinal Design With Ecological Momentary Assessments

Abstract: Background Recent studies have found bi-directional relations between stress and sleep. However, few studies have examined the daily associations between stress and electroencephalography (EEG) measured sleep. Purpose This study examined the temporal associations between repeated ecological momentary assessments of stress and EEG-estimated sleep. Methods Nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…Simply put, if participants experience very similar experiences and very similar sleep on all days, we can learn little about the relationship between these two variables in a daily observational study like BSETS, which effectively uses participants as their own controls. However, previous studies [ 20 , 22 , 24 ] reported moderate intraclass correlation coefficients, that is, indicators of within-individual similarity, of daily experiences and sleep variables, suggesting that in practice, we will see sufficient within-individual variance in BSETS to enable meaningful analyses.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Simply put, if participants experience very similar experiences and very similar sleep on all days, we can learn little about the relationship between these two variables in a daily observational study like BSETS, which effectively uses participants as their own controls. However, previous studies [ 20 , 22 , 24 ] reported moderate intraclass correlation coefficients, that is, indicators of within-individual similarity, of daily experiences and sleep variables, suggesting that in practice, we will see sufficient within-individual variance in BSETS to enable meaningful analyses.…”
Section: Resultsmentioning
confidence: 92%
“…However, some outstanding issues remain. First, while some studies [ 22 , 24 ] used EEG to provide an objective measurement of sleep, this is not standard procedure and this may be problematic as self-reports of sleep are only moderately accurate [ 25 ]. To our knowledge, no daily observational study used quantitative EEG to establish the link between daily experience and sleep, although based on experimental studies [ 81 , 82 ] it is highly expected that daily experiences will affect waveforms during the subsequent nights, for example because richer experiences require additional synaptic downscaling through increased slow-wave activity [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent publication used a similar device to test temporal relationships between EEG measured sleep and daytime stress over two weeks in a non-clinical sample. They found that several sleep markers predicted next-day stress level (Yap et al, 2022 ) indicating feasibility of such methods.…”
Section: Discussionmentioning
confidence: 99%